A critical review of the prospects and challenges of Hepatitis B therapeutic vaccines - Abdullahi Hudu, Shuaibu; Osman, Amira; Jebreel Ibrahim Abu-Shoura, Esra’a; Olayiwola Jimoh, Abdulgafar (Trends in Immunotherapy, 2024)
Hepatitis B therapeutic vaccines hold great promise in the treatment of chronic Hepatitis B virus (HBV) infection. However, like any medical intervention, they also face certain prospects and challenges which forms the aim of this critical review. Therapeutic vaccines offer a targeted approach to manage chronic Hepatitis B infections, aiming to stimulate the immune system to recognise and eliminate infected cells. The potential to halt disease progression holds promise for preventing severe liver diseases associated with chronic Hepatitis B, such as cirrhosis and hepatocellular carcinoma. Therapeutic vaccines, if effective, could contribute to a more equitable distribution of treatment options globally, especially in resource-limited settings. Hepatitis B therapeutic vaccines may play a crucial role in preventing vertical transmission, reducing the global incidence of perinatal HBV infections and improving maternal-child health outcomes. Diverse vaccine platforms and combination strategies, including immunomodulation and checkpoint inhibitors, are advancing, optimising immunogenicity, and eliciting strong immune responses. Tailoring therapeutic vaccines to individual patients based on genetic considerations may enhance efficacy, recognizing the genetic diversity of Hepatitis B. Therapeutic vaccines need to align with global health goals related to infectious disease elimination, contributing to broader efforts to reduce the burden of Hepatitis B worldwide. While Hepatitis B therapeutic vaccines hold significant promise in transforming the management of chronic infections, addressing challenges related to access, viral variability, and long-term monitoring is crucial for their successful integration into global healthcare strategies.